Association of blood vitamin A with osteoarthritis: a nationally representative cross-sectional study - Wu, Ao; Wu, Ning-ning; Xu, Peng-hui; Jin, Yao; Yang, Zhi-kai; Teng, Jia-wen (Frontiers in Nutrition, 2024)
Objectives:Vitamin A plays an important role in health, especially regarding its impact on bone tissue. Vitamin A can lead to bone damage and deformity, thus becoming an important causative factor in osteoarthritis. In this study, we aimed to evaluate the association of serum vitamin A with osteoarthritis. Methods: We included participants who self-reported whether they had OA in NHANES 2001-2006 and NHANES 2017-2018 to explore the association and dose-response relationship between vitamin A concentration and risk of osteoarthritis through weighted multivariate logistic models and restricted cubic splines. Sensitivity and stratification analyses were also used to assess the robustness of the results. Results: A total of 18,034 participants were included in this study, and a linear association between serum vitamin A concentration and osteoarthritis risk was observed. The OR of osteoarthritis was 1.22 (95% CI: 0.98,1.52), 1.40 (95% CI: 1.05,1.85), and 1.47 (95% CI: 1.14,1.91) for participants in the second, third, and fourth quartiles, respectively, compared with the lowest vitamin A reference group. Similar results were obtained when sensitivity and stratification analyses were performed. Conclusions: Serum vitamin A is positively associated with osteoarthritis risk. Within a certain range of vitamin A concentrations, vitamin A is a protective factor against osteoarthritis, beyond which it becomes a causative factor for osteoarthritis.